A protocol for professional nurses regarding the management of nurse initiated management of antiretroviral therapy (NIMART) in the Ehlanzeni District, Mphumalanga Province, South Africa - Sekatane, Patricia Thato (University of Limpopo, 2014)
The purpose of the study was to develop protocol for professional nurses regarding NIMART management that is based on data and specific challenges that are faced in the Ehlanzeni district by professional nurses. A quantitative, descriptive and cross-sectional research design was used for this study. The population consisted of all professional nurses who are NIMART trained, managing and initiating patients on ARV’s at primary health care clinics. Systematic random sampling method was used to select 135 respondents. Data was collected through the self-developed questionnaire. The questionnaire was pre tested. Reliability was ensured through self-administered questionnaire and with the guide of literature review. The questionnaire was also pre tested by conducting a pilot study. Validity was ensured through undertaking extensive literature review, giving operational definitions of concepts, questionnaires were given to supervisors, questions constructed according to the objectives of the study and congruence was ensured between research questions, objectives, findings and recommendations. Data analysis was done through descriptive studies, using SPSS statistics 21.0 programme of data analysis with the assistance of the statistician. The findings indicate that challenges faced by professional nurses regarding nurse initiated and management of antiretroviral therapy are be lack of professional nurses, fear of infecting themselves while treating HIV positive patients, patients do not come on their return dates, encountering problems when they trace defaulters and shortage of retroviral drugs. The study recommends that staff shortage should be addressed, medicine supply should be monitored, a competent HIV trained doctor should be appointed and dedicated outreach team should be appointed. Keywords: NIM-ART, HIV/AIDS, Professional nurse
Thesis (M.Cur.) -- University of Limpopo, 2014
Keywords: Professional nurse; NIM-ART; HIV/AIDS; Nursing services - Personnel management.; HIV/AIDS